Penyuluhan Hukum Pencegahan dan Pelaporan Pinjaman Online Ilegal di Desa Ngawen Kecamatan Muntilan (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
The legal counseling activity on the technical aspects of preventing and reporting Ilegal online lending in Ngawen Village, Muntilan District, was motivated by the increasing number of Ilegal online lending cases that harm the community due to low legal and digital literacy. Rural communities often become victims because they do not understand the differences between legal and Ilegal loans and are unaware of the proper reporting mechanisms. This activity aims to provide residents with legal understanding regarding online lending regulations, improve digital literacy so that the community can identify Ilegal applications, and train residents to be courageous and capable of reporting Ilegal online lending practices to the relevant authorities. The implementation methods included socialization through interactive lectures, distribution of handout materials, and question-and-answer sessions. The activity was attended by 15 residents of Ngawen Village and featured two presenters from the Faculty of Law, Universitas Muhammadiyah Magelang. The results showed an increase in participants’ understanding of the characteristics of Ilegal online lending, its socio-economic impacts, and the reporting procedures to the Financial Services Authority (OJK), the Ministry of Communication and Informatics (Kominfo), and the police. Participants also gained a better understanding of the importance of protecting personal data and verifying the legality of financial applications before using them. In conclusion, this counseling activity successfully enhanced the community’s legal awareness and digital literacy, fostering a more vigilant and legally empowered society capable of protecting itself from Ilegal online lending practices in the digital era.